2012
DOI: 10.1100/2012/218679
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Mould and Aflatoxin Contamination in Tarhana, a Turkish Fermented Food

Abstract: Tarhana is a popular traditional Turkish cereal-based fermented food product mainly produced at home or at home-scale level. Some certain mould species can grow even at low moisture and pH values and produce aflatoxins in food. This study was conducted to determine aflatoksin levels in tarhana. For this purpose, a total of 138 tarhana powder samples were collected from bazaars in Istanbul and analyzed for aflatoxins, mould contamination, and some physco-chemical parameters. As a result, 32 out of 138 tarhana s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Data presented in Table (3) also showed that one sample of Kishk out of five samples contained a moderate concentration (300 -500 µg/Kg) of aflatoxin B 1 . These results agree with Colak et al (2012) who found that 23.2% of tarhana samples (turkish cereal-based fermented food product like kishk) collected from Istanbul were contaminated by aflatoxins in the range of 0.7-16.8 μg/kg. However, Eighty percent of Kishk samples were negative for mycotoxin.…”
Section: Samplesupporting
confidence: 92%
“…Data presented in Table (3) also showed that one sample of Kishk out of five samples contained a moderate concentration (300 -500 µg/Kg) of aflatoxin B 1 . These results agree with Colak et al (2012) who found that 23.2% of tarhana samples (turkish cereal-based fermented food product like kishk) collected from Istanbul were contaminated by aflatoxins in the range of 0.7-16.8 μg/kg. However, Eighty percent of Kishk samples were negative for mycotoxin.…”
Section: Samplesupporting
confidence: 92%
“…Although there are several studies on total aflatoxin, aflatoxin B1 (AFB1), ochratoxin A (OTA) level (Arıcı 2000; Colak et al 2012;Ozden et al 2012) and microbiological quality of tarhana Erbas et al 2005;Settanni et al 2011;Sengun & Karapinar 2012), there is no study on the AFM1 level of Tarhana chips. Thus, the objective of this study was to investigate AFM1 contamination of Tarhana chips and to determine colour, proximate composition and textural properties.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the presence of mycotoxins in fermented foods (i.e., iru , ogi , ogi baba , ugba and ogiri ) cannot be undermined. Even though fermentation could play a role in the degradation or detoxification of mycotoxins in foods, there are increasing reports of mycotoxins in fermented foods [9,10,11]. In Nigeria, there are no in-depth studies that report multiple mycotoxin contamination in the selected fermented foods, hence the need for this study.…”
Section: Introductionmentioning
confidence: 99%